Analysis of the Implementation of Nationalist Values in Pencak Silat Schools - Ayu Saptira Rahmawati; Andy Supriady; Nancy Trisari Schiff (Journal of Physical and Outdoor Education, 2026)
This study aims to analyze the application of nationalist values ​​in pencak silat schools in Indonesia. Through a qualitative approach with a qualitative descriptive method, respondents in this study were school administrators, coaches and martial artists/students at the Sinar Pusaka Tunggal Pencak Silat School in Bandung City. Data were collected through interviews, observations, and documentation of administrators, coaches, and martial artists/students of the school. This study examines the implementation of nationalist values ​​such as love of the homeland, preserving culture, the spirit of patriotism, willingness to sacrifice, and creativity which are applied in the activities and teachings of pencak silat schools, both through routine training and championships. The results of the study show that the Sinar Pusaka Tunggal Pencak Silat School in Bandung City consistently instills nationalist values ​​to its members, which are reflected in loyalty to the nation's culture, pride in the national language, and strengthening unity and defending the country. These values ​​not only strengthen national identity, but also play a role in building national character and resilience amidst the challenges of globalization and threats to the integrity of the country. This study recommends the need to strengthen the role of pencak silat schools as a means of forming nationalist attitudes through the development of programs and guidelines for nationalist values ​​that are integrated into every training activity.